Stakeholder Based Transformational Leadership Model for Improving Teacher Performance in Elementary Schools - Nuri Handayani; Ismail; Suparta Rasyid; Rini Susanti Gulo (LPPM Undiksha, 2025)
Basic education in island regions faces serious challenges, including limited infrastructure, restricted access to teachers’ professional development, and fluctuating work motivation, all of which contribute to low teacher performance. These conditions require school leadership capable of transforming structural constraints into organizational strengths. This study aimed to analyze, evaluate, and interpret principals’ transformational leadership practices in improving teacher performance in 3T regions. The study employed a descriptive qualitative approach with a case study design. The research participants consisted of eight individuals, including school principals and teachers directly involved in leadership and instructional processes. Data were collected through semi-structured interviews, passive participant observation, and document analysis, using interview guidelines, observation sheets, and document checklists as research instruments. Data analysis was conducted thematically using the interactive model of Miles and Huberman, encompassing data reduction, data display, and conclusion drawing. The findings indicate that principals’ transformational leadership is manifested through strengthening shared vision and motivation, providing individualized professional mentoring, and offering intellectual stimulation that encourages instructional innovation and reflective teaching practices. The study concludes that principals’ transformational leadership plays a strategic role in enhancing teacher professionalism and performance in island regions. The implications of this study suggest that strengthening transformational leadership capacity should be a priority in principal development programs to foster collaborative, adaptive, and quality-oriented school ecosystems in 3T regions.